STUDIES OF THE RELATIONSHIP BETWEEN COAL PETROLOGY AND GRINDING PROPERTIES - Trimble A.S.; Hower J.C. (My University, 2003)
The maceral and microlithotype composition of selected coals has been investigated with respect to the grinding properties, specifically Hardgrove grindability index (HGI), of the coals. The study expands upon previous investigations of HGI and coal petrology by adding the dimension of the amount and composition of the microlithotypes. Coal samples, both lithotypes and whole channels, were selected from restricted rank ranges based on vitrinite maximum reflectance: 0.75-0.80% Rmax, 0.85-0.90% Rmax and 0.95-1.00% Rmax. In this manner, the influence of petrographic composition can be isolated from the influence of rank. Previous investigations of high volatile bituminous coals demonstrated that, while rank is an important factor in coal grindability, the amount of liptinite and liptinite-rich microlithotypes is a more influential factor. In this study, we provide further quantitative evidence for the influence of microlithotypes on HGI and, ultimately, on pulverizer performance.
Keywords: COAL; HARDGROVE GRINDABILITY; KENTUCKY; PETROLOGY; MICROLITHOTYPE